(untitled) (Revista Electrónica REDINE, 2018)
Human beings are the main source for creating value and generating results in an organization. The result of this premise is the need to direct efforts to identify, develop and connect human talent. The present study was oriented to propose strategies for the development of social and emotional competences as a tool in the management of teaching performance. It was framed in the feasible project modality, supported by a field research with a non-experimental design of descriptive level. Three questionnaire-type instruments were used for data collection. The study population consisted of thirty (30) people: Teachers, Area Coordinators and Head of Department. For the tabulation and analysis of the data, descriptive statistics were used. The results were presented in tables and were illustrated by means of bar graphs. The findings show that implementing strategies aimed at the development of social and emotional competencies, will result in an improvement of levels of teacher performance, also represents a way to promote a set of changes to adapt the skills of future graduates to the demands of the Society of knowledge, technology and information.